Pricing carbon consumption: A review of an emerging trend - Clayton Munnings; William Acworth; Oliver Sartor; Yong-Gun Kim; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Nearly every carbon price regulates the production of carbon emissions, typically at midstream points of compliance, such as a power plant. Over the last six years, however, policymakers in Australia, California, China, Japan, and Korea implemented carbon prices that regulate the consumption of carbon emissions, where points of compliance are farther downstream, such as distributors or final consumers. This article aims to describe the design of these prices on carbon consumption, understand and explain the motivations of policymakers who have implemented them, and identify insights for policymakers considering whether to price carbon consumption. We find a clear trend of policymakers layering prices on carbon consumption on top of prices on carbon production in an effort to improve economic efficiency by facilitating additional downstream abatement. In these cases, prices on carbon consumption are used to overcome a shortcoming in the price on carbon production: incomplete pass-through of the carbon price from producers to consumers. We also find that some policymakers implement prices on carbon in an effort to reduce emissions leakage or because large producers of carbon are not within jurisdiction. Since policymakers are starting to view prices on carbon consumption as a strategy to improve economic efficiency and reduce emissions leakage in a way that is compatible with local and international law, we expect jurisdictions will increasingly implement and rely upon them.
Keywords: D12; H23; Q54; 330; Carbon pricing; Consumption based policy; Review